Individual Preparedness and Response to Chemical, Radiological, Nuclear, and Biological Terrorist Attacks The Reference Guide - Davis, Lynn E. (RAND Corporation, 2003)
The guide focuses on simple steps individuals can take to prepare for and respond to terrorist attacks with chemical, biological, radiological ("dirty bomb") and nuclear weapons. The guides contain both preparatory steps and specific response guidance. This includes what individuals will experience, what their goals should be, and what they should do during each type of attack